(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Poly(N-isopropylacrylamide) (PNIPAAm) is a new type of smart thermo-sensitive macromolecule material that is characterized by a sudden precipitation on heating, switching from a hydrophilic to a hydrophobic state. In this paper, using the self-made equipment of atmospheric pressure plasma vapor treatment running in the environment of argon, PNIPAAm was deposited separately to Polybutylene Terephthalate (PBT) melt-blown nonwovens and Polyester (PET) fabrics. It was found that the wettability and water permeability were significantly modified by changing the temperature above and below the Lower Critical Solution Temperature (LCST), according to the data derived from measurements of water contact angle, water permeability time and Scanning Electron Microscopy (SEM) images. Considering human body temperature is close to the LCST, these results are valuable for further application to thermo-sensitive textile materials.